2018
DOI: 10.18203/2394-6040.ijcmph20182417
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status of adolescent school girls residing in rural areas of Dharwad district, India: a cross sectional study

Abstract: Background: Adolescence is a period with rapid growth drive and demands higher nutrition. Improving Nutritional status of rural adolescent girls becomes the cornerstone of community’s nutritional status and target intervention for breaking intergeneration cycle of nutritional deficiencies. The objective of the study was to determine nutritional status and study the demographic factors affecting nutritional status of rural adolescent girls in Dharwad district.Methods: A cross-sectional study was carried out amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The prevalence of under nutrition in eastern Sudan and Saudi Arabia was (38.3%) and 19.2% respectively which is lower than this finding and besides, study conducted in India indicated that 69% of adolescent girls were under nutrition in Bhopal district which is higher than my finding. 22,24,26 This might be due to the difference in socioeconomic background between the areas. The of this study is higher than the studies in Babile (21.6%), in Adama city (21.3%), in Agarfa, Bale Zone (13.68%), in Adwa town 21.4% and in Mekele city 37.8%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of under nutrition in eastern Sudan and Saudi Arabia was (38.3%) and 19.2% respectively which is lower than this finding and besides, study conducted in India indicated that 69% of adolescent girls were under nutrition in Bhopal district which is higher than my finding. 22,24,26 This might be due to the difference in socioeconomic background between the areas. The of this study is higher than the studies in Babile (21.6%), in Adama city (21.3%), in Agarfa, Bale Zone (13.68%), in Adwa town 21.4% and in Mekele city 37.8%.…”
Section: Discussionmentioning
confidence: 99%
“…12 Another study conducted in Belagavi showed that the prevalence of thinness in adolescent girls was 62% and prevalence of overweight was 2% and another, study conducted in Dharwad district, India showed that the nutritional status of adolescent girl residing in rural area was BMI, 25.2% of girls were under-nourished and 3.7% were over nourished. 23,24 In addition, study done in arar city, kingdom of Saudi Arabia on adolescent girl nutritional status shown that 19.2% were underweight. 25 The rational of this study is to know adolescence girl under nutrition and associated factors in the study area.…”
Section: Introductionmentioning
confidence: 99%
“…Observation recorded in the present study is similar to the findings reported by Sen and Lakhawat [15] in the Assessment of the nutritional status of rural and urban adolescent girls in the Udaipur district where the mean weight of urban respondents was higher than the mean weight of rural respondents. Similarly, a study by Pavithran and Bant [17] revealed that approximately 14.9 per cent of adolescent females residing in rural areas exhibited a body weight that was below the recommended range for their respective age groups.…”
Section: Somatic Status Of Urban and Rural Respondentsmentioning
confidence: 94%
“…The author suggested that it can be further improved with school-based nutrition education, nutrition sensitive interventions and comprehensive community based programs to reach both the students and their families. Pavithran and Bant (2018) revealed the nutritional status of adolescent school girls residing in rural areas of Dharwad district, India. They studied their socio demographic profile, anthropometric measurements (height, weight and BMI) and dietary pattern of rural adolescent girls.…”
Section: Methodsmentioning
confidence: 99%